YouTube for Enhancing EFL Students’ Motivation in Vocabulary Acquisition: A Systematic Review - Ardianti, Amelia Putri; Faricha Maula Chabibah (Universitas Al-Qolam Malang, 2025)
YouTube videos, as an accessible and context-rich visual medium, have emerged as a valuable tool in English as a Foreign Language (EFL) education, particularly for vocabulary acquisition. This study systematically reviews and analyzes the use of YouTube videos to enhance students’ motivation in vocabulary development. Following the PRISMA 2020 guidelines for systematic literature reviews, peer-reviewed articles were retrieved from Scopus and Google Scholar databases. A total of 13 studies were selected based on their relevance to the integration of YouTube in EFL teaching and learning. The findings indicate that YouTube provides engaging and contextualized content that supports learner autonomy, enhances motivation, and improves vocabulary acquisition. Despite its demonstrated benefits, the review reveals several gaps: limited research on teacher perspectives, insufficient exploration across different educational contexts, and underutilization of diverse research methodologies. The study underscores the pedagogical potential of YouTube for designing student-centered, interactive learning experiences while highlighting the need for professional development to support effective implementation. Future research is recommended to broaden the investigation to include educators’ experiences, address practical challenges, and examine YouTube’s integration across multiple language skills, thereby supporting more inclusive and effective language learning practices. Overall, this review emphasizes that YouTube is a promising tool for enhancing vocabulary learning and learner engagement in EFL contexts, with implications for both educational practice and future research.